'In the name of justice and compassion': animal protection in Italy during the Liberal Age (1861-1914). Issue 3 (1st September 2017) - Guazzaloca, Giulia
Abstract : This essay reconstructs the emergence of a growing sensitivity towards animal welfare in Italy during the so-called 'liberal' years. An examination of the origins and activities of animal protection societies, the debate on use of animals for scientific experimentation, and the earliest provisions for animal protection, reveals a growing concern for animal welfare in Italy too during the course of the twentieth century. This was channelled by the liberal-bourgeois values of the time: public decency, moderation, and goodwill towards animals as well as humans were all seen as signs of 'civilisation' and 'progress'. It was claimed that foreign influence, particularly British, was of vital importance in such developments in Italy, including both the thoughts of the anti-vivisectionists and the work and propaganda of the societies for animal protection. This essay also examines the 1913 Law, which was the first important Italian legislation governing animal welfare and protection. Italian summary: Il saggio ricostruisce l'emergere della sensibilità zoofila in Italia durante l'età liberale. Seguendo le origini e le attività delle società protezioniste, il dibattito sulla sperimentazione animale e le prime norme sulla tutela animale, mostra che anche in Italia l'interesse per la condizione degli animali si fece strada nel corso del XIX secolo attraverso i valori della cultura liberal-borghese: decoro pubblico, moderazione, benevolenza, anche verso i non umani, erano visti come segno di 'civiltà' e 'progresso'. Si spiega anche come in Italia furono decisive le influenze straniere, soprattutto britanniche, sia nelle riflessioni degli antivivisezionisti, sia nell'operato e nella propaganda delle associazioni zoofile. Il saggio si sofferma infine sulla legge del 1913 che costituì il primo importante intervento della legislazione italiana sulla protezione animale.